The Influence of Problem Based Learners on Students' Mathematical Thinking Ability in Understanding and Applying Polya Stages - Nurtamam, Mohammad Edy; Jannah, Ana Naimatul (eScience Humanity Journal, 2024)
The purpose of this study is to determine the influence of problem-based learning on students' mathematical ability in understanding and applying polya stages. This research is a type of quantitative research with a meta-analysis approach. The sample of this study comes from 13 studies indexed by Sinta or Scopus published in 2021-2024. The data collection technique is direct observation with the PRISMA data selection method. The data analysis in this study is a quantitative analysis by calculating the effect size value with the help of the JASP application. The results of the study concluded that the problem-based learning model provided a significant impact on students' mathematical thinking ability in understanding and applying polya stages with a value of (d = 1.042; p < 0.001) with a medium effect size category